Ultimate behaviour and design of post-tensioned composite slabs. (1st November 2017) - Ranzi, Gianluca; Ostinelli, Andrea
Highlights: Investigating the ultimate behaviour of post-tensioned composite slabs. Experimental measurements on simply-supported post-tensioned composite slab tests. Design model to predict the ultimate response of post-tensioned composite slabs. Validation of the design model against available experimental test results. Abstract: Post-tensioned composite slab systems consist of concrete slabs poured on thin-walled profiled steel sheeting and prestressed soon after casting. This paper presents six experimental tests that investigate the influence of different parameters on the ultimate behaviour of post-tensioned composite slabs. For this purpose, the samples were tested to failure in a simply-supported configuration. The parameters considered in this study included the slab thickness, the number of prestressing strands, the span length and the continuity of the profiled sheeting. A design model is also presented for the evaluation of the ultimate moment capacity by extending the applicability of procedures currently available for composite and prestressed floor slabs. The proposed theoretical approach was validated against the measurements presented in the paper and available in the literature. The comparisons carried out between the experimental measurement and the calculated capacities showed close agreement.